Fuel Efficiency Comparison of PBN and ILS Approach Procedures at Sam Ratulangi Airport - M'Azzuri, Banni Yulia; Indriyanto, Toto; Sembiring, Javensius (Indonesian Journal of Aerospace, 2024)
This study evaluates the efficiency of approach procedures at Sam Ratulangi International Airport-Manado by comparing Required Navigation Performance (RNP) under Performance-Based Navigation (PBN) with the Instrument Landing System (ILS) as a conventional procedure. A simulation using the BlueSky ATM Simulator was conducted with 30 aircraft instances for each approach, utilizing real-time FlightRadar24 speed data to ensure operational realism. The analysis focused on three key metrics: distance flown, time spent, and fuel consumption. Results show that implementing of PBN procedures reduces distance flown by 15%, flight time by 15% and fuel consumption by 14% compared to ILS, demonstrating improved operational efficiency. This research provides a quantitative assessment of PBN systems’ effectiveness in optimizing approach procedures, supporting aviation sustainability, and reducing operational costs.